Hubungan antara Penguasaan Mufradat dengan Kemampuan Menerjemah Pada Mata Pelajaran Bahasa Arab Siswa MTs Darul Ulum Rembang Pasuruan - Nurrokhmatulloh; Wahyuni, Siti (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2025)
Arabic Vocabulary Ability is part of the ability to master a language component that aims to form sentences in Arabic. The purpose of the problem in this study is to determine whether there is a correlation between Vocabulary mastery and translation ability in Arabic subjects for class VIII students of MTs Darul Ulum Rembang Pasuruan. From the mastery of Vocabulary and the ability to translate are interrelated to the achievement of Arabic language learning. Based on the conceptual framework, both have indicators and outcomes that affect Arabic language learning. So there is a significant influence between Vocabulary mastery and translation ability in Arabic subjects. This type of research uses quantitative research with a pre-experimental method. The sampling technique is nonprobability with a purposive sampling technique. The population in this study were all class VIII students totaling 20 people. Based on the results of the research that has been conducted, there is a significant correlation between vocabulary mastery and translation ability with a significance value of 0.000 <0.05, so the hypothesis is that Ho is rejected and Ha is accepted, meaning that there is a correlation between vocabulary mastery and translation ability in the Arabic language subject of class VIII students of MTs Darul Ulum Rembang Pasuruan